PENGEMBANGAN E-LKPD BERBASIS KARAKTER MENGGUNAKAN KAHOOT PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SD - Imam, Muhammad Khairul; Gandamana, Apiek; Sirait, Albert Pauli; Siregar, Waliyul Maulana; Purnomo, Try Wahyu (Jurnal Merah Putih Sekolah Dasar, 2024)
This research aims to produce character-based E-LKPD using Kahoot in the Pancasila Education Subject for Class IV SDN 056001 Karang Rejo. Research and development is carried out using the ADDIE model which consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The subjects of this research were design expert validators, material experts and educational practitioners, namely teachers and 34 class IV students at SDN 056001 Karang Rejo. Data collection instruments use interviews, questionnaires and tests. The results of the research obtained a feasibility score by the design expert validator with a percentage of 88.75% in the "Very Feasible" category, the material expert validator obtained a percentage of 77.90% in the "Feasible" category and the practicality test by educational practitioners obtained a percentage score of 95.38 % in the "Very Practical" category. The students' pre-test and post-test results based on the results of the N-Gain analysis obtained an average N-Gain percent score of 58.36 in the "Effective" category. Thus, character-based E-LKPD using Kahoot in elementary school Pancasila Education subjects is very feasible, very practical and effective for use by students in the learning process.